Improving digitalization and financial literacy in wood carving craftsmen in Siangan Village, Gianyar - Luh Diah Citra Resmi Cahyadi; Eka Putri Suryantari (Community Empowerment, 2024)
Community service activities in Siangan Village, Gianyar aim to improve the quality of digitalization and financial understanding for wood carving craftsmen. The methods used include outreach, training and group discussions (FGD) involving the PKM team, Sentir Foundation and craftsmen. The results show an increase in understanding and practice of digitalization using Instagram and Google to inform business biodata. Apart from that, craftsmen are also able to increase social media content that is more interesting and informative. There is increased understanding of simple financial records and awareness of the importance of financial reports for business development. To evaluate the craftsmen's understanding, a pre-test and post-test were carried out using the Wilcoxon Test, resulting in a significant difference between the pre-test and post-test (Z = -2.820, Asymp. Sig. (2-tailed) = 0.005 < 0.05).